THE WORK “ZILZALA (EARTHQUAKE)” MOLDO KILIC SHAMYRKAN UULU AS A HISTORICAL NARRATIVE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
For the first time, the article analyzes the work of Moldo Kylych Shamyrkan uulu, published in 1911 in the Kyrgyz language, about the earthquake of 1910. The analysis is carried out in order to confirm the historicity of the work known to the Turkic world, the events described in it with documents, as well as to confirm the veracity and the possibility of using the work as a historical source.
Keywords: earthquake, earthquake, creation, ruin, consequence, catastrophe